The Effects of Dietary Supplementation of Saccharomyces cerevisiae Fermentation Product During Late Pregnancy and Lactation on Sow Productivity, Colostrum and Milk Composition, and Antioxidant Status of Sows in a Subtropical Climate - Chen, Jun; Zhang, Yufeng; You, Jinming; Song, Hanqing; Zhang, Yinzhi; Lv, Yantao; Qiao, Hanzhen; Tian, Min; Chen, Fang; Zhang, Shihai; Guan, Wutai (Frontiers in Veterinary Science, 2020)
This study aimed to evaluate the effects of dietary supplementation of Saccharomyces cerevisiae fermentation product (SCFP) during late pregnancy and lactation on sow productivity, colostrum and milk composition, and antioxidant status of sows in a subtropical climate. The study was a 2 × 2 factorial treatment design where the first factor was environmental THI level [Low THI (08:00 - 19:00: 70.76 ± 0.45, 19:00 - 08:00: 67.91 ± 0.18, L-THI) or High THI (08:00 - 19:00: 75.14 ± 0.98, 19:00 - 08:00: 68.35 ± 0.18, H-THI], and the second factor was dietary treatment (supplemented with or without 3 kg/t SCFP). A total of 120 sows were randomly allotted to the four treatments (n=30). The feeding trial was conducted from 85-d post-breeding until 21-d post-partum. Compared with L-THI group, sows from H-THI group had lesser individual piglet birth weight, individual piglet weight at weaning, preweaning average daily gain of piglets, average daily feed intake of sows during lactation, and protein percentage in 14-d milk. Additionally, sows from H-THI group had lesser antioxidant status, indicated by lesser serum total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) activity at parturition; lesser serum T-AOC and glutathione peroxidase (GSH-Px) activity at 14-d post-partum, as well as lesser SOD activity in colostrum. Compared with sows fed the control diet, sows fed the SCFP diet had greater number of piglets weaned, litter weight at weaning, and preweaning average daily gain of piglets. Moreover, sows fed the SCFP diet had improved antioxidant status as indicated by higher serum T-AOC at parturition, and lesser malondialdehyde (MDA) content in colostrum and 21-d milk. In conclusion, H-THI negatively affected the productivity, milk composition, antioxidant status, and lactation feed intake of sows. Dietary supplementation of SCFP partially alleviated the adverse effects of H-THI, by improving lactation performance and antioxidant status of sows without influencing reproductive performance and colostrum and milk composition in a subtropical climate.